1954
DOI: 10.1113/jphysiol.1954.sp005036
|View full text |Cite
|
Sign up to set email alerts
|

The use of sacs of everted small intestine for the study of the transference of substances from the mucosal to the serosal surface

Abstract: A preparation of isolated small intestine of the rat or golden hamster (Mesocricetus auratus) is described which permits convenient measurement ofrespiration and glycolysis during periods of active transference of substances across the wall. The difficulty of adequate oxygenation is overcome by everting a piece of intestine, tying it at both ends and filling it with sufficient fluid to distend the wall. The eversion exposes the highly active mucosa to the well-oxygenated suspending medium, while the distension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
330
2
4

Year Published

1970
1970
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,142 publications
(338 citation statements)
references
References 10 publications
2
330
2
4
Order By: Relevance
“…Everted sacs were prepared using the method of Wilson and Wiseman (1954). The rat was killed with anaesthetic ether.…”
Section: Tissue Levels Of Deoxycholatementioning
confidence: 99%
“…Everted sacs were prepared using the method of Wilson and Wiseman (1954). The rat was killed with anaesthetic ether.…”
Section: Tissue Levels Of Deoxycholatementioning
confidence: 99%
“…Preparation of Everted Xacs Everted sacs were prepared by a modification of the procedure described by Wilson and Wiseman [24]. Male albino random-bred Sabra rats (150-200 g) starved overnight were used.…”
Section: Purification Of Li'olatesmentioning
confidence: 99%
“…The method provides valuable information about the drug absorption mechanisms as well as the effects of substances increasing or decreasing intestinal absorption [19,20]. It has been suggested that drug transporter molecules are distributed unevenly throughout the small intestine, and the absorption of some drugs has been reported to be higher in the distal parts of the intestine (the ileum and jejunum) compared to the proximal intestinal segments [5,6,21].…”
Section: Discussionmentioning
confidence: 99%